2007
DOI: 10.1111/j.1399-0012.2007.00749.x
|View full text |Cite
|
Sign up to set email alerts
|

Our experience in liver transplantation in patients over 65 yr of age

Abstract: Results in patients >65 yr are comparable to those <65 yr if older LT candidates are carefully selected. Overimmunosuppression should be avoided in older candidates, as its effects could worsen the pre-existing diseases common in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 24 publications
7
50
0
1
Order By: Relevance
“…The cause was hepatitis B in 180 (43%), cryptogenic in 66 (16%), hepatitis C in 64 (14%), alcoholic in 58 (14%), non-alcoholic stereohepatitis in 34 (8%), and primary bilary cirrhosis or primary sclerosing cholangitis in 22 patients (5%). The median MELD score was 16 (IQR, [12][13][14][15][16][17][18][19][20]. All patients received the right lobe of their donor in a standard technique.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The cause was hepatitis B in 180 (43%), cryptogenic in 66 (16%), hepatitis C in 64 (14%), alcoholic in 58 (14%), non-alcoholic stereohepatitis in 34 (8%), and primary bilary cirrhosis or primary sclerosing cholangitis in 22 patients (5%). The median MELD score was 16 (IQR, [12][13][14][15][16][17][18][19][20]. All patients received the right lobe of their donor in a standard technique.…”
Section: Resultsmentioning
confidence: 99%
“…All of the patients had at least one complication of their liver cirrhosis, such as hepatic encephalopathy, variceal bleeding, or spontaneous bacterial peritonitis. The median model for end-stage liver disease (MELD) score was 13 (interquartile range [IQR], [11][12][13][14][15][16][17] and the median World Health Organization (WHO) performance status was preoperatively three (IQR, 3-3.5). The measured median skeletal muscle area, using preoperative computed tomography scan, was 98 cm 2 (IQR, 95-125) in men and 68 cm 2 (IQR, 61-87) in women.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three recent studies are especially noteworthy: all demonstrated 5‐year survival rates greater than 70% and mortality rates comparable to those of younger populations 29, 30, 39. Many centers continue to view the transplant candidacy of 60‐ and 70‐year‐old patients with a great deal of scrutiny, however, because data contrary to these reports exist in abundance 13, 17, 23, 24, 32, 35, 40‐46. In fact, higher recipient age has been independently associated with increased mortality after transplantation, with an HR of 2.1 being ascribed to each 10‐year increase 22.…”
Section: Discussionmentioning
confidence: 99%
“…The morbidity and mortality of OLT recipients increase with age, particularly among patients more than 60 years old 16, 17. The excess mortality is due largely to nonhepatic causes,16 with CAD a major contributor during the intraoperative, early postoperative, and later phases 18, 19.…”
Section: Cad In Esld Patients and Its Significance In Clinical Managementioning
confidence: 99%